MOEIN, F., MAJIDI, R., KHAZAEI, Z. & ALIPOUR, S. (2023) Tulipa sarvestanica (Liliaceae), a new species from south-western Iran. Phytotaxa 630 (1): 87–92. - Moein, Fatemeh; Majidi, Ramiar; Khazaei, Zahra; Alipour, Sajad (Phytotaxa, 2024)
Erratum